Digital Financial Literacy in the Fintech Era: A Literature Review - Sispurwanto, Yedi; Yelmi, Harmi; Nurmita, Septia; Rahmat, Hayatul Khairul (Journal of Current Research in Humanities, Social Sciences, and Business, 2024)
The rapid expansion of financial technology (fintech) has fundamentally transformed the way individuals’ access, use, and manage financial services. Digital platforms such as mobile banking, peer-to-peer lending, digital wallets, robo-advisors, and cryptocurrencies have increased financial inclusion while simultaneously introducing new risks related to data security, consumer protection, and financial decision-making (Arner et al., 2017; Gomber et al., 2017). In this context, digital financial literacy has emerged as a critical capability for individuals to navigate increasingly complex financial ecosystems. This literature review synthesizes international peer-reviewed studies on digital financial literacy in the fintech era, focusing on conceptual development, key dimensions, determinants, and socio-economic implications. The findings indicate that digital financial literacy extends beyond traditional financial knowledge by incorporating digital skills, technological awareness, and behavioral competencies (Morgan & Trinh, 2019; OECD, 2020). Higher levels of digital financial literacy are consistently associated with improved financial behavior, increased adoption of fintech services, reduced vulnerability to fraud, and enhanced financial well-being (Lusardi & Mitchell, 2014; Xiao & O’Neill, 2016). However, substantial disparities persist across age, income, education, and geographic location. This review concludes that strengthening digital financial literacy requires coordinated policy interventions, inclusive education strategies, and responsible fintech design to ensure that digital finance contributes to sustainable and equitable economic development.